2020
DOI: 10.1039/c9bm01455a
|View full text |Cite
|
Sign up to set email alerts
|

Sustained protein therapeutics enabled by self-healing nanocomposite hydrogels for non-invasive bone regeneration

Abstract: The self-healing nanocomposite hydrogel for sustained release of BMP-2 to enhance bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Bone transplantation is the main method for the treatment of bone damage but it is becoming more and more difficult to obtain a donor while the easier allogeneic transplantation often leads to an immune rejection and a big spending. [155,156] Filling the defected bones with the hydrogels carrying functional cells and inducing the new bone growth in situ has become a recent good strategy to address www.advancedsciencenews.com www.mrc-journal.de these appeals. There were several self-healing polysaccharide hydrogels applied to repair the damaged structure and function of the bones, [157,158] and the coral hydroxyapatite (CHA), which has a structure similar to cancellous bone tissue and is often used as a bone graft substitute, has been chosen for the fabrication of such a scaffolding hydrogel material.…”
Section: Cell Therapymentioning
confidence: 99%
“…Bone transplantation is the main method for the treatment of bone damage but it is becoming more and more difficult to obtain a donor while the easier allogeneic transplantation often leads to an immune rejection and a big spending. [155,156] Filling the defected bones with the hydrogels carrying functional cells and inducing the new bone growth in situ has become a recent good strategy to address www.advancedsciencenews.com www.mrc-journal.de these appeals. There were several self-healing polysaccharide hydrogels applied to repair the damaged structure and function of the bones, [157,158] and the coral hydroxyapatite (CHA), which has a structure similar to cancellous bone tissue and is often used as a bone graft substitute, has been chosen for the fabrication of such a scaffolding hydrogel material.…”
Section: Cell Therapymentioning
confidence: 99%
“…reported that hyaluronic acid–Dextran–Laponite RD (HD‐LAP) hydrogels embedded with rat bone marrow mesenchymal stem cells (rBMSC) and BMP‐2 were able to promote new tissue generation after 8 weeks postimplantation in contrast to control groups. [ 69 ] Similarly, a Laponite RD‐alginate‐methylcellulose bioink was fabricated by Cidonio et al., and its biocompatibility and osteogenic capacity were subjected to in vitro and in vivo tests. [ 70 ] Once its effectiveness in vitro and ex vivo was demonstrated, in vivo subcutaneous implantation of BMP‐2 loaded and human bone marrow stromal cells (HBMSC) laden ones were conducted.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…On the one hand, there are studies that conclude that nanoclays are capable of regenerating bone thanks to the inducing medium they create via mineral dissolution products, [ 61,67,73,77,84 ] while other studies have focused more on the ability of nanomaterials to sustain the release of drugs or growth factors. [ 49,69,71,86 ]…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Another example of self-healing hydrogel nanocomposite for bone tissue regeneration based on hyaluronic acid and dextran has been reported [ 120 ]. This hydrogel could be in situ formed through a spontaneous Schiff-base reaction.…”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
“… ( A ) In vivo study of the evaluation of calvarial bone defect regeneration at 4 and 8 weeks after the implantation and ( B ) analysis of bone volume/total volume (BV/TV) and bone mineral density (BMD) (* p < 0.05, ** p < 0.01 and *** p < 0.001). Reproduced with permission from [ 120 ] (Copyright RSC 2020). …”
Section: Figurementioning
confidence: 99%